Estimation of groundwater favorable zones in Pothohar region for management of water demand in area - Alam, Nayab; Tahir, Naveed; Imran, Muahammad; Hanif, Muhammad (Journal of Pure and Applied Agriculture, 2023)
In this study geophysical technique of electrical resistivity method was employed with integrated approach of using geospatial techniques for identification of groundwater favorable zones in the Pothohar region of Punjab, Pakistan. Favorable zones of groundwater occurrence in this area were delineated using resistivity survey datasets. Resistivity survey was conducted at about 240 different points in all the districts of the area. Schlumberger electrode configuration method was used and 2D resistivity survey technique was employed in this study for which adjoining borehole records were also collected. Area had presented up to five geoelectrical layers and geological units. Groundwater bearing rocks were evident at around depth of 100m and beyond with the resistivity values fluctuated between 100 Ωm to 250 Ωm. Whereas low resistivity values of less than 65Ωm in deep zones indicated the presence of clay mixed with shale which extended up to the depth of 180m and marked as no aquifer zones. Water favorability map was then generated by integrating the resistivity survey results with the geology of Pothohar region. Final groundwater prospect map exhibited the presence of two groundwater potential area found in third and fourth geoelectric layers. Shallow aquifers were found at the sites of alluvium deposition of quaternary period, with depth of 3 to 25 meters whereas deep water zones were demarcated at the depth of 70m and beyond 160 meters in the areas of sandstone formations. © 2022 Department of Agricultural Sciences, AIOU